1997
DOI: 10.1212/wnl.49.2.358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interferon beta-1a on neurologic disability in relapsing multiple sclerosis

Abstract: The primary clinical outcome for the IFN beta-1a clinical trial underestimated clinical benefits of treatment. Results in this report demonstrate that IFN beta-1a treatment is associated with robust, clinically important beneficial effects on disability progression in relapsing MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(88 citation statements)
references
References 8 publications
2
82
1
3
Order By: Relevance
“…This trial also reported a reduction in the unconfirmed 1-point EDSS worsening over the first 2 years of the study (Ϫ28%; p ϭ 0.037). Also, in a secondary analysis of data from the extension phase of this trial, 23 after excluding determinations made during acute attacks, these authors reported a significant reduction in the unconfirmed 1.5 point EDSS progression rate over 3 years in the treated patients compared with control subjects (Ϫ48%; p ϭ 0.004) using survival analysis methods. This last analysis, however, is of uncertain reliability.…”
Section: Analysis Of the Evidence Immunomodulatory Treatments Intermentioning
confidence: 93%
See 1 more Smart Citation
“…This trial also reported a reduction in the unconfirmed 1-point EDSS worsening over the first 2 years of the study (Ϫ28%; p ϭ 0.037). Also, in a secondary analysis of data from the extension phase of this trial, 23 after excluding determinations made during acute attacks, these authors reported a significant reduction in the unconfirmed 1.5 point EDSS progression rate over 3 years in the treated patients compared with control subjects (Ϫ48%; p ϭ 0.004) using survival analysis methods. This last analysis, however, is of uncertain reliability.…”
Section: Analysis Of the Evidence Immunomodulatory Treatments Intermentioning
confidence: 93%
“…[18][19][20][21][22][23][24][25][26][27] Thus, in general, when comparing the different findings of these trials, both the magnitude of the reported effects on clinical and MRI outcomes, as well as their statistical significance, seem to be greater with increasing dosages of IFN␤. Nevertheless, because of differences in trial design, differences in the MS populations studied, and the fact that the results were obtained in independent clinical trials, this observation can only be considered as weak (Class III) evidence of a dose response.…”
Section: Analysis Of the Evidence Immunomodulatory Treatments Intermentioning
confidence: 99%
“…Tolerance of the drug was acceptable, considering the inherent discomfort of the IM injection route. Subsequent re-analysis of the data by the investigators 38 included a change of EDSS greater than two points, or sustained progression by one point for one year, with the conclusion that the previous results underestimated the effect of IFNβ-1a. Further post-hoc analysis revealed benefit in some areas of neuropsychological testing and degree of brain atrophy in patients treated with IFNβ-1a.…”
Section: Dovepressmentioning
confidence: 99%
“…The effect of interfering with the signaling pathways of these cytokines have been tested by the development of a variety of anticytokine agents some of which are currently in the market or are being assessed in clinical trials of autoimmune diseases. Some of these anti-cytokine compounds include etanercept/enbrel, adalimumab/humira, infliximab/remicade, certolizumab pegol/cimzia, alefacept /amevive, avonex, and betaseron, which are used as therapeutic agents in autoimmune diseases such as RA, psoriasis, MS and Crohn's disease [160][161][162][163][164]. These drugs have shown beneficial in subsiding inflammation associated with some of the autoimmune diseases; however, they were effective only in a subset of patients.…”
Section: N O T F O R D I S T R I B U T I O Nmentioning
confidence: 99%